Scaling up the Med-South Lifestyle Program in public health settings to reduce chronic disease risk: a hybrid implementation-effectiveness study - Carmen D. Samuel-Hodge; Carmen D. Samuel-Hodge; Lisa Pham; Kiira Lyons; Lindy B. Draeger; Li Jiang; Feng-Chang Lin; Rachel Ram; Jennifer Leeman (Frontiers in Public Health)
IntroductionMajor disparities persist in heart disease, diabetes, and obesity, with rates highest among those living in the southeastern and central parts of the US. Intervening to improve lifestyle behaviors represents an opportunity to address health inequities. Although the scientific rationale for lifestyle interventions is robust, evidence is limited on how to implement these interventions at scale.MethodsUsing a type 3 hybrid implementation-effectiveness design, we evaluated a statewide scale-up trial implementing the Med-South Lifestyle Program in mostly rural community health centers and health departments across North Carolina, in the southeastern US. Implementation outcomes were measured at the site level and program effectiveness outcomes were assessed by physiologic and behavioral changes at the participant level. Descriptive statistics and paired t-tests comprised our statistical analyses.ResultsWe invited 200 public health sites to participate in the study and 28 (14%) expressed interest. Among those expressing interest, 21 (75%) signed a Memorandum of Agreement. The statewide scale-up resulted in the enrollment of 95% (19/20) of the proposed sites−13 health departments (68%) and six community health centers. The majority of the 235 study participants who started the program were adults self-identifying as non-Hispanic White (45%) or non-Hispanic Black (37%); 11% identified as Hispanic and 5% as American Indian. Most participants were female (88%), with a mean age of 51 years, and educational attainment of a 2- or 4-year college degree (57%). Implementation outcomes included 17 sites (89%) retained throughout the study and a 79% participant retention rate. Program uptake was high, with 87% of planned counseling sessions and 83% of follow-up calls completed. For our effectiveness outcomes we observed small but statistically significant changes in weight of −2.3 lbs. Similarly, systolic but not diastolic blood pressure was reduced significantly (−2.3 mm Hg). There was a significant increase in the mean weekly intakes of nuts and healthy fats, improved daily fruit-vegetable-bean scores, and a decrease in daily sugar-sweetened beverage intake. For sedentary behaviors, daily sitting time was significantly reduced.ConclusionsThese results show successfully adapted implementation and delivery approaches to fit Med-South into the context of public health settings during the COVID-19 pandemic.Trial RegistrationClinicalTrials.gov: NCT05067816, October 5, 2021.